A Simplified Mechanical Model and Analysis for the Settlement Deformation of Buried Pipelines Caused by Open-Cut Excavation - Yulin Lu; Jinze He; Yinuo Jing; Xiaoran Chen (Applied Sciences, 2023)
This study aims to reveal the deformation characteristics of buried pipelines and the effects of various parameters on settlement displacement using the analytical analysis method. A simplified mechanical model for the settlement displacement of buried pipelines is proposed with the theory of the Winkler model, and the sensitivity impacts of various parameters are performed by comparing them with those given by other cases. The rationality of the proposed approach is verified by a comparison with previous cases, and it also turned out that the present method performed better than the other two methods in the literature in its overall tendency of settlement displacement and error precision. The parameter analysis results of this study indicate that the maximum settlement displacement of the buried pipelines only increases linearly with the increase in ground displacement. Other parameters such as the subgrade modulus and calculated length increase to a certain threshold; the maximum settlement displacement will remain stable. However, the diameter and elastic modulus of the pipelines only have a small effect on the maximum settlement displacement of the pipelines, so they are not a sensitive factor and these effects can be ignored. In addition, an engineering example of pipeline deformation in a deep foundation pit from open-cut excavation is researched to verify the practicality of this present method.